2009
DOI: 10.1211/jpp.61.06.0005
|View full text |Cite
|
Sign up to set email alerts
|

l-Carnosine: multifunctional dipeptide buffer for sustained-duration topical ophthalmic formulations

Abstract: Functional synergy between excipients in gellan gum formulations buffered with l-carnosine has potential for topical ocular dosage forms with sustained precorneal residence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Carnosine (β-alanyl-L-histidine), a naturally-occurring endogenous di-peptide, is present in surprisingly large amounts in long-lived human tissues. Numerous lines of evidence have pointed to the multi-functional significance of carnosine in the human body: (1) serves as a physiological buffering agent [30] , [116] , [117] and a metal ion (e.g., zinc and copper) chelator [118] – [120] ; (2) possessing anti-aging functions [121] , [122] , and free-radical scavenging activity [123] , [124] ; (3) capable of delaying senescence [125] and extending the life-span of cultured human fibroblasts [36] ; (4) able to kill transformed cells and protect cells against aldehydes and amyloid peptide fragment [126] . Other investigators have concluded that carnosine exhibits a well-documented anti-glycating activity against the glycation of proteins, including low-density lipoproteins, glucose degradation products, esterase, and histones [127] – [130] .…”
Section: Discussionmentioning
confidence: 99%
“…Carnosine (β-alanyl-L-histidine), a naturally-occurring endogenous di-peptide, is present in surprisingly large amounts in long-lived human tissues. Numerous lines of evidence have pointed to the multi-functional significance of carnosine in the human body: (1) serves as a physiological buffering agent [30] , [116] , [117] and a metal ion (e.g., zinc and copper) chelator [118] – [120] ; (2) possessing anti-aging functions [121] , [122] , and free-radical scavenging activity [123] , [124] ; (3) capable of delaying senescence [125] and extending the life-span of cultured human fibroblasts [36] ; (4) able to kill transformed cells and protect cells against aldehydes and amyloid peptide fragment [126] . Other investigators have concluded that carnosine exhibits a well-documented anti-glycating activity against the glycation of proteins, including low-density lipoproteins, glucose degradation products, esterase, and histones [127] – [130] .…”
Section: Discussionmentioning
confidence: 99%
“…GG may either exist in its native form or upon alkaline hydrolysis originate the so called low-acyl GG [22], both forms retaining the capability to crosslink into hydrogels in the presence of mono-, di-and trivalent cations [24,25]. This polysaccharide has been proven suitable for the production of microbeads [26][27][28] or for the production of formulations for the sustained delivery of relevant drugs [29][30][31][32][33][34][35]. Due to its resemblance with the extracellular matrix glycosaminoglycan composition [36] it has gathered also important attention in the field of tissue engineering and regenerative medicine [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%